Here are my answers to the given questions above:
Part 1. Here is my example of a real life scenario that describes what is happening. Let us say, I have 2 cookies and the bottle of milk costs 11 dollars, and 3 cookies and 4 bottles of milk cost 24 dollars.
Part 2.
y=11-2x
3x+4(11-2x)=24
3x+44-8x=24
-5x=-20
x=4
y=11-8
y=3
Therefore, each cookie costs 4 dollars, and a bottle of milk costs 3 dollars.
Hope this answer helps. Let me know if you need more help next time.
<span>
</span>
Answer:
8 ≤ $45
Step-by-step explanation:
Given:
People younger than 8 get in for $45.
Now we can assume that the cost given might be to enter in the garden or might be in fair or might be at museum or might be at a zoo which is $45 for people which are younger than 8.
Now we can say for people younger than 8 means people or children who are of 8 years or who are below 8 years or say less than 8 years.
Hence we can say people who are less than or equal to 8 get in for $45
So the inequality equation becomes.
8 ≤ $45
Answer: $12.60 per hour
Step-by-step explanation:
5% of 12 is 0.60
12 + 0.60 = 12.60
Hope you have a great day
X=the number we have to find.
This expression "2(x+9)" is when the sum of a number and nine is doubled.
If the result is seven less than the number, we will have: x-7
We can suggest the following equation:
2(x+9)=(x-7)
2x+18=x-7
2x-x=-7-18
x=-25
answer: the number would be: -25.
<h2>
Answer:</h2>
cos 28°cos 62°– sin 28°sin 62° = 0
<h2>
Step-by-step explanation:</h2>
From one of the trigonometric identities stated as follows;
<em>cos(A+B) = cosAcosB - sinAsinB -----------------(i)</em>
We can apply such identity to solve the given expression.
<em>Given:</em>
cos 28°cos 62°– sin 28°sin 62°
<em>Comparing the given expression with the right hand side of equation (i), we see that;</em>
A = 28°
B = 62°
<em>∴ Substitute these values into equation (i) to have;</em>
<em>⇒ cos(28°+62°) = cos28°cos62° - sin28°sin62°</em>
<em />
<em>Solve the left hand side.</em>
<em>⇒ cos(90°) = cos28°cos62° - sin28°sin62°</em>
⇒ 0 = <em>cos28°cos62° - sin28°sin62° (since cos 90° = 0)</em>
<em />
<em>Therefore, </em>
<em>cos28°cos62° - sin28°sin62° = 0</em>
<em />
<em />